IMPLEMENTASI MANAJEMEN STRATEGI DALAM JOFTER GROUP (CO-WORKING DAN VIRTUAL OFFICE): : IMPLEMENTASI MANAJEMEN STRATEGI DALAM JOFTER GROUP (CO-WORKING DAN VIRTUAL OFFICE) - Darmawan, Roslinda Jasmine; Putra, Vico Rahmatullah; Wahyono, Budi; Miawati, Tita (CV ODIS, 2025)
Strategic management plays a crucial role in the development of co-working spaces and virtual offices, especially in navigating an increasingly competitive market. This study aims to examine the implementation of strategic management in the context of Jofter Group as a provider of co-working and virtual office services. The research method used is a literature review, analyzing strategic management theories, success factors in service-based businesses, and relevant case studies. The findings indicate that the success of strategic management implementation in Jofter Group depends on strategy formulation, operational implementation, as well as evaluation and adaptation to market changes. The implications of this study can serve as recommendations for co-working and virtual office managers in optimizing their business strategies.